2017
DOI: 10.1093/mnras/stx2676
|View full text |Cite
|
Sign up to set email alerts
|

A multi-wavelength analysis of the diffuse H ii region G25.8700+0.1350

Abstract: We present a multiwavelength investigation of the H ii region G25.8700+0.1350, located in the inner part of the Galaxy. In radio continuum emission, the region is seen as a bright arcshaped structure. An analysis of the Hi line suggests that G25.8700+0.1350 lies at a distance of 6.5 kpc. The ionized gas is bordered by a photodissociation region which is encircled by a molecular structure where four molecular clumps are detected. At infrared wavelengths, the region is also very conspicuous. Given the high level… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Proposed examples of triggered star formation abound in the literature over a variety of scales. In particular, the high quality infrared observations from the Spitzer and Herschel space observatories over the last decade and a half have provided abundant support for the actual existence of triggered star formation along the edges of bubble-like HII regions (Deharveng & Zavagno 2011;Samal et al 2014;Liu et al 2016;Gama et al 2016;Cichowolski et al 2018). Examples at larger scales where star formation appears to have been caused by expanding supershells seen in HI in the disk of our Galaxy also exist (Megeath et al 2003;Oey et al 2005;Arnal & Corti 2007;Lee & Chen 2009), although the evidence is more elusive, largely due to confusion and crowdedness along the line of sight.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed examples of triggered star formation abound in the literature over a variety of scales. In particular, the high quality infrared observations from the Spitzer and Herschel space observatories over the last decade and a half have provided abundant support for the actual existence of triggered star formation along the edges of bubble-like HII regions (Deharveng & Zavagno 2011;Samal et al 2014;Liu et al 2016;Gama et al 2016;Cichowolski et al 2018). Examples at larger scales where star formation appears to have been caused by expanding supershells seen in HI in the disk of our Galaxy also exist (Megeath et al 2003;Oey et al 2005;Arnal & Corti 2007;Lee & Chen 2009), although the evidence is more elusive, largely due to confusion and crowdedness along the line of sight.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, several analysis of the energy values involved in the formation of these regions show that many highmass stars seem to be missing or have not been detected (e.g. Cichowolski et al 2018). On the other side, observational studies have confirmed that massive stars are not usually isolated but are, in fact, members of binary systems or other stellar groups (Roberts 1957;Maíz-Apellániz 2004;Barbá et al 2017).…”
Section: Introductionmentioning
confidence: 97%
“…The structure and physical properties of molecular clouds can be significantly influenced by feedback from massive stars (>8 M e ), such as outflows, radiation pressure, stellar winds, and supernova explosions (Zinnecker & Yorke 2007;Raskutti et al 2017;Cichowolski et al 2018). Radiation from H II regions and expansion of supernova remnants can create expanding shells in their surroundings and the expanding shells can sweep up diffuse molecular gas into dense shells which may subsequently undergo fragmentation and form a new generation of stars (Whitworth et al 1994;Kim et al 2017).…”
Section: Introductionmentioning
confidence: 99%